Exploring the Teaching Assistance Program Implementation and Value Conversion of Language and Social Science Education Students - Sibua, Sulami; Muhammad, Darlisa; Ruslan, Hasnur (Journal of Languages and Language Teaching, 2024)
The teaching assistance activities in teacher education colleges are intended to train students early on to understand the real learning process in schools. They are guided by teachers in schools to experience and observe all teacher activities in the school. Therefore, the research aims to describe the conditions of the implementation of teaching assistance for students majoring in Language Education and Social Science Education at educational units in the city of Ternate. The research issues are focused on problems in the implementation of teaching assistance activities and the compatibility of program application with credit hours conversion and the grades programmed by students. The method used is a case study with data collection techniques including observation, interviews, questionnaires, and documentation conducted at the educational units where teaching assistance is implemented in Ternate, as well as the Coordinator of the Indonesian Language, English Language Education, and IPS Education programs for the 2022-2023 academic year. In addition to the faculty team, students majoring in Indonesian Language Education are involved in this research. The research results show that: first, teaching assistance is very important to be carried out so that students can directly master various teaching skills and the programmed courses, as there is thorough preparation by students, mentor teachers, and supervising faculty. Second, the conversion of grades from student programs shows a similarity in the assessment process according to the guidelines and detailed assessment rubrics in line with the learning outcomes of the courses programmed by students. Third, due to strict control, every implementation of the teaching assistance program is carried out well, and program participants are enthusiastic about participating in teaching assistance for the completion of their studies with maximum quality.